INCREASING KNOWLEDGE AND SKILLS OF POSYANDU CADRES AS AN EFFORT TO PREVENT STUNTING IN BREMI VILLAGE, PROBOLINGGO REGENCY - Septyani Prihatiningsih; Indah Lutfiya; Erwin Dyah Nawawinetu (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: One of the global nutrition problems that are the focus in developing countries is stunting. Probolinggo is one of the regions that accounts for the second highest prevalence of stunting in East Java at 39.9% exceeding the maximum WHO limit of 20%. Bremi Village, Krucil District is a village in the highlands of Probolinggo Regency which has a stunting prevalence of more than 30%. Objective: this activity is scheduled as an effort to prevent stunting in Bremi Village, Krucil Probolinggo District. Method: This activity is carried out in 4 stages starting from planning, implementing, observing and evaluating activities. Results: Community service activities received positive appreciation with the provision of stunting kits, early detection of stunting training, competition for making local Supplementary Food (PMT) and stunting early detection competitions through measuring body weight, height and reading KMS. The results of the survey of respondents' knowledge about stunting after education got an average score of 80.This is reinforced by the average skills of respondents from the competition for making local food PMT and early detection of stunting, which showed satisfactory results with a value range of 70 to 80. Conclusion: The useful aspect of this activity is quite high. Posyandu cadres receive education and skills for early detection of stunting independently, thus supporting stunting prevention in Bremi Village.